Firm size and participation in the international economy: Evidence from Bangladesh - Ben Shepherd (Asian Development Bank Institute (ADBI), 2020)
This paper examines the trade participation of Bangladesh's manufacturing firms using a three-year panel. It distinguishes between extensive and intensive margin effects using a Heckman sample selection model. Particular attention is paid to the role of imported intermediates and inward foreign direct investment (FDI) in promoting export development. While there is a strong association between export performance and firm size, these two indicators have a positive impact on trade participation at the intensive margin for firms of all sizes, and importing intermediates also have a positive impact on trade participation at the extensive margin. An analysis of marginal effects from the model shows that small firms experience the smallest export boost from importing and inward FDI, although the effect is still quantitatively large. From a policy perspective, the paper highlights the importance of international openness and global value chain linkages as drivers of export success, including for smaller firms. It also stresses the possible alternative ways through which small and medium-sized enterprises (SMEs) may participate in the international economy, such as by exporting indirectly. Reconciling legitimate policy interest in SME trade with the universal empirical finding that larger firms participate to a greater degree in the trading economy should be an important objective of future research.
Keywords: F13; F15; O24; 330; trade policy; foreign direct investment; manufacturing; Bangladesh; small and medium-sized enterprises; sample selection model